Small molecule additive for low-power accumulation mode organic electrochemical transistors - Nightingale,J; Pitsalidis,C; Pappa,A-M; Tan,E; Stewart,K; Owens,RM; Kim,J-S (Journal of Materials Chemistry C, 2020)
A small molecule additive, dodecylbenzenesulfonate (DBSA), is added to the electrolyte in OECTs to improve the device performance.